2017
DOI: 10.3389/fnins.2017.00596
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Interplay of Vitamin B1 and B6 Metabolism with Cognition, Brain Structure, and Functional Connectivity in Older Adults

Abstract: Aging is associated with brain atrophy, functional brain network reorganization and decline of cognitive performance, albeit characterized by high interindividual variability. Among environmental influencing factors accounting for this variability, nutrition and particularly vitamin supply is thought to play an important role. While evidence exists that supplementation of vitamins B6 and B1 might be beneficial for cognition and brain structure, at least in deficient states and neurodegenerative diseases, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 128 publications
0
31
0
Order By: Relevance
“…Risk ratio or hazard ratio data are rounded to 2 decimal places. B6 on cognitive function in older adults with normal vitamin B6 blood levels [55].…”
Section: Apoe 4 Allelementioning
confidence: 99%
See 1 more Smart Citation
“…Risk ratio or hazard ratio data are rounded to 2 decimal places. B6 on cognitive function in older adults with normal vitamin B6 blood levels [55].…”
Section: Apoe 4 Allelementioning
confidence: 99%
“…Additionally, both vitamin B6 and folate are involved in the synthesis of several key neurotransmitters, and folate deficiency has been related to oxidative stress and DNA damage in neurons [68,69]. However, one study showed that a positive association with cortical folding was detectable in a population taking supplemental B vitamins, but cognitive function did not improve [55]. The uncertain mechanism by which B vitamins affect cognition may potentially explain the lack of association between the concentrations or intake of vitamin B12, folate, or vitamin B6 and cognition in the current meta-analysis.…”
Section: Apoe 4 Allelementioning
confidence: 99%
“…A doubling of serum levels during the washout period was observed exclusively with thiamine. If this effect is already apparent in healthy people, then it is even more valuable, e.g., in older people [24] whose poor vitamin B 1 metabolism leads to processing deficits and further to a lack of vitamin B 1 in the brain [25]. Sufficient supply is also required among others, for children [26], celiac disease patients [27], or alcoholics [28].…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study of older adults (aged 55–85 years) demonstrated that despite the normal to high thiamine blood levels of all study participants, insufficient metabolization of thiamine could result in an effective thiamine metabolite deficiency in the target tissue (ie, brain). 30 …”
Section: Discussionmentioning
confidence: 99%